The Influence of Emotional Branding and Online Community Support on Brand Loyalty Mediated by Consumer Value Perceptions - Abdillah, Fatimah; Heriyana, Heriyana; Hartati, Bella (SEIKO : Journal of Management & Business, 2023)
This research investigates the complex dynamics of brand loyalty within the organizational framework of PT Bandung Indah Gemilang. It examines the interplay between emotional branding, online community support, consumer value perceptions, and brand loyalty among employees. The research reveals that emotional branding significantly influences brand loyalty directly and indirectly through consumer value perceptions. Conversely, online community support has a direct impact on brand loyalty, but its influence is not significantly mediated by consumer value perceptions. These nuanced findings highlight the importance of tailored strategies in optimizing emotional connections and online community engagement to foster brand loyalty within the workforce. The study offers practical insights for organizational practitioners aiming to enhance employee commitment and brand allegiance through refined approaches to emotional branding and online community support. Keywords: Emotional Branding, Online Community Support, Brand Loyalty, Consumer Value Perceptions